Dream home : the Property Brothers' ultimate guide to finding & fixing your perfect house - Scott, Jonathan, 1978 April 28-; Scott, Drew, 1978- (Houghton Mifflin Harcourt, 2016)
"Jonathan and Drew Scott have taken HGTV by storm with their four hit shows, Property Brothers, Property Brothers at Home, Buying & Selling, and Brother vs. Brother. The talented duo's good-natured rivalry, playful banter, and no-nonsense strategies have earned the popular twins millions of devoted fans who have been anxiously waiting for a Scott Brothers book. Dream Home is a comprehensive source, covering the ins and outs of buying, selling, and renovating a house, with hundreds of full-color photos throughout. The brothers cover numerous topics including the hidden costs of moving, savvy negotiating tactics, and determining your home must-haves. Other handy features include a calendar of key dates for finding the best deals on home products and a cheat sheet of worth-it fix-its. Look inside for a wealth of information on attaining what you want--on time and on budget. Dream Home also includes all the tips and tricks you won't see on TV, making it a must-have resource not just for fans but for any current or aspiring homeowner,"--Amazon.com.